Assessing the Viability of Establishing a Dairy Milk Business in the Village Unit Cooperative of Gandusari District, Blitar Regency: A Feasibility Analysis - Maya Novitawati; Livia Windiana; Bambang Yudi Ariadi (Universitas Muhammadiyah Malang, 2023)
Milk is a vital animal-derived food product, along with meat and eggs, for human consumption. In Indonesia, the dairy industry is dominated by small and medium-sized dairies. Dairy cows are a significant source of animal protein, and their primary product is milk. In the North of Blitar Regency lies the sub-district of Gandusari, where dairy cow milk is produced in the villages under the coverage of the Village Unit Cooperative called KUD